Laban: A guide figure between dance/movement therapy and drama therapy. (February 2018) - Young, Jessica; Wood, Laura L.
Highlights: Laban Movement Analysis supports the expansion of both role and movement repertoire. Laban's Effort Theory contributes to a deepening of Landy's role method and Role Theory. Collaboration between dance/movement therapists and drama therapists is beneficial. Abstract: The field of Creative Arts Therapies stands to benefit from ongoing support and collaboration between practices that comprise the disciplines. Both dance/movement therapy (DMT) and drama therapy (DT) draw upon a creative, action-oriented, and embodied approach to psychotherapy; however, a review of the literature indicates minimal collaboration on theory and research between the two. Through an in-depth review of the literature and a supporting case study, a theoretical model is constructed proposing that Laban Movement Analysis (LMA) and Role Theory and role method may be a natural point of intersection, enriching each discipline and presenting implications for creative arts therapies praxis.